MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBUAT UKIRAN DENGAN JOB SHEET PADA PROSES PEMBELAJARAN DI KELAS IX. 3 SMPN 2 TANJUNG MUTIARA - IDRAWATI, Drs. Efrizal, M.Pd, Drs. SyafrilR, M.Sn (Serupa The Journal of Art Education, 2014)
The journal is motivated by low ability students in the class carving IX.3 SMP 2 Tanjung Mutiara. One reason is the lack of creative teachers in selecting the appropriate model with the characteristics of the material being taught has not been able to improve students' skills in making carvings. This study aims to improve students' skills in making carving is by using job sheets.Research data obtained from an increase in the ability of students as seen from the first cycle and second cycle. For the observed ability is active students increased from 7.5% to 18%, the ability of the student interaction increased from 7.5% to 32%, the ability of working techniques increased from 7% to 40%, the ability of the form displayed on the 7% increase to 28%, the ability of the neatness of 14% increased to 34%, finishing capabilities of 12% increased to 28%. Thus, learning to make carving the job sheet showed significant improvement and was successful in improving students' ability to make carvings.The results of this study indicate that the use of job sheets can improve students' skills in making carvings. This is evident from the increase in learning outcomes of each cycle is implemented.Keywords: The ability of students, job sheets, learning